Pengaruh Angry Cat Pose terhadap Nyeri Punggung pada Ibu Hamil Trimester III di Puskesmas Gunungpati - Rindang Kasih Parawansha Hariyoko; Nella Vallen; Qomariyah Qomariyah (Lembaga Pengembangan Kinerja Dosen, 2025)
Introduction: Back pain during pregnancy is a problem that is often experienced by pregnant women and is complex because it involves not only physical changes, but also psychological aspects. Changes in body biomechanics, weight gain, and shifting of the center of gravity due to uterine enlargement are the main factors that trigger pain complaints, especially in the lower back area. This condition can have a negative impact on the quality of life of pregnant women, interfere with daily activities, and even worsen emotional states due to the emergence of anxiety, fear, and stress if not managed properly. Treatment of back pain in pregnant women can be done through safe non-pharmacological methods, one of which is prenatal yoga. Yoga practice for pregnant women has been proven to provide benefits in the form of relaxation, posture improvement, and increased muscle elasticity. One of the effective movements is the Angry Cat Pose because it is able to stretch the back muscles, improve blood circulation, and reduce pressure on the lower spine. Objective: This study aims to analyze the effect of Angry Cat Pose exercise on the intensity of back pain in pregnant women in the third trimester. Methods: This study used a quasi-experimental design with a one group pretest-posttest design. The study sample consisted of 31 pregnant women in the third trimester with complaints of back pain who visited the Gunungpati Health Center. The research instrument was in the form of a questionnaire, while the data analysis was carried out using the Wilcoxon test with a significance level of <0.05. Results: The results showed a significant effect of the Angry Cat Pose exercise on the reduction of back pain in pregnant women in the third trimester with p=0.000. After the intervention, the majority of respondents experienced a decrease in pain to the mild category on a scale of 1–3. Conclusion: The Angry Cat Pose exercise has been shown to be effective in reducing back pain in third trimester pregnant women, so it can be recommended as a safe, simple, and routine nonpharmacological intervention under the supervision of health workers.